The hefty price you pay for manual triage. Issue 12 (December 2021) - MacKenzie, Thomas
Abstract : With the number of security threats increasing at an alarming rate, businesses need to be proactive and vigilant to protect themselves. Remediating every vulnerability is just not an option so cyber security teams must prioritise and tackle vulnerabilities in order of criticality to keep their companies safe.